The Political Economy of Hospital Rate Regulation in Maine - Wihry, David; Fralich, Julie; Schneiter, Ellen (Maine Policy Review, 1993)
Ten years ago, Maine established a health care finance board to regulate hospital rates. But the concerns that prompted the regulatory system, access and cost, have not abated. In this article, former Maine Health Care Finance Commission chair David Wihry, and former Commission staffers Julie Fralich and Ellen Jane Schneiter examine the economic and political influences that have affected the state’s efforts to regulate hospital costs.